Effect of exercise on specific indicators of physical fitness and physical development of military student artilleryman - V.B. Klimovich; S.V. Romanchuk (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The features of professional roles ground artillery ground forces in peacetime. Presented educational experiment on the application of special physical exercises to improve performance standards for the combat work of students. In the experiment were involved 52 students. Students also performed the test - bringing gun D - 30 from traveling to combat. Found that special training exercise significant influence on the performance of physical fitness of students. It is noted that the physical exercises for strength and power endurance develop gunners in precisely those physical qualities that are necessary for the performance of their direct duties. It is noted that the exercises for strength and strength endurance is necessary to give priority to the preparation of artillery of the Army.